Effects of fermented cow urine on the growth and quality of katuk (Sauropus androgynus) accessions from West Java, Indonesia - ARIFAH RAHAYU; NUR ROCHMAN; WINI NAHRAENI; YULIAWATI YULIAWATI (Asian Journal of Agriculture, 2025)
Abstract. Rahayu A, Rochman N, Nahraeni W, Yuliawati. 2025. Effects of fermented cow urine on the growth and quality of katuk (Sauropus androgynus) accessions from West Java, Indonesia. Asian J Agric 9: 831-843. This study examined the growth, yield, and nutritional quality of katuk using local germplasm and natural nitrogen sources. The objective was to evaluate the performance of ten katuk accessions from West Java, Indonesia, and to assess the potential of fermented cow urine as a supplementary nitrogen source relative to urea. A factorial completely randomized design with three replications was employed, consisting of ten accessions (Sarampad, Maleber1, Maleber2, Kadudampit1, Kadudampit2, Gegerbitung, Dramaga, Cinangneng1, Cinangneng2, and Katulampa) and six fertilizer compositions (0% cow urine + 100% Urea; 100% cow urine + 0% Urea; 75% cow urine + 25% Urea; 50% cow urine + 50% Urea; 25% cow urine +75% Urea; 0% cow urine + 0% Urea). Sarampad, Maleber1, and Maleber2 exhibited superior fresh and dry harvest weight, vitamin C, chlorophyll a and b content, while maintaining low nitrate accumulation. Plant height under 100% cow urine, shoot number and vitamin C under 25% cow urine + 75% urea, and chlorophyll a, b, and total chlorophyll under 50% cow urine + 50% Urea were higher than under 100% Urea, with superiority values of 14.7%, 19.0%, 20.2%, 14.6%, 18.2%, and 15.9%, respectively. These findings indicate that fermented cow urine may serve as a low-cost supplementary nitrogen source for katuk; however, its use as a full replacement for synthetic nitrogen fertilizer requires further validation under field conditions.